The Relationship Between Vocabulary Mastery and Reading Ability - Putri Haris Tia; Yulia Agustina; Andri Suherman; M. Adib Nazri (Journal of Classroom Action Research, 2026)
This study aimed to examine the relationship between vocabulary mastery and reading ability among eleventh-grade students at MA Ar-Raufiyah Lendang Jaran, East Lombok. Employing a quantitative correlational design, the research sought to determine the degree of association between the two variables without manipulation. The sample consisted of 20 students, selected through purposive sampling based on their active participation in English classes. Data were gathered using two instruments: a vocabulary mastery test and a reading comprehension test, both validated for reliability with a coefficient value of 0.789. The data were analyzed statistically using the Pearson Product Moment correlation test. The results revealed a strong and significant positive correlation (r = 0.789, p < 0.05) between students’ vocabulary mastery and their reading ability. This finding indicates that students with a higher level of vocabulary mastery tend to achieve better comprehension in English reading tasks. The study highlights the importance of integrating vocabulary instruction into reading activities to improve students’ overall English proficiency.